ADDITIVE TECHNOLOGIES AND THEIR PERSPECTIVES IN EDUCATION - L. A. Lipnitski; T. V. Pilgun (Системный анализ и прикладная информатика, 2018)
The article describes the role of additive technologies in the development of innovative thinking among students, spheres of use of 3D-printers and prototypes created by means of 3D technology. It is specified that additive technologies allow to accelerate operations on design and prototyping considerably, allow students to estimate results of their research, to increase interest in learning, to change methods of presentation of their research for protection. The article presents the most perspective and available for use in education technologies. The FDM technology being the most available prints using the plastic thread melted in a thermohead, but has rather low resolution depending on the speed of plotting of layers. The SLA technology becoming more available to a wide circle of users lately uses photopolymeric resins for printing, has high accuracy and speed of printing that allows to create small and high-precision details and to imitate different materials. The article mentions the active use of 3D-printers in foreign training centers. It describes the creation of the own 3D-printer in Belarusian National Technical University, the creation of laboratory of computer simulation and rapid prototyping in Polotsk State University, the use of 3D-printers in Belarusian State Technological University, Belarusian State University, Belarusian State University of Informatics and Radioelectronics, Brest State Technological University. The positive impact from implementation of additive technologies in educational and R&D life of higher education institutions of Belarus and need of their wide use for educational process is specified. The article points that use of additive technologies at universities will change a mentality of students, their approach to study and creation of new ideas.